FACTORS INFLUENCINGINFANT IMMUNIZATIONIN FIRDAUS VILLAGE, SEI RAMPAH DISTRICT - Nanin Juliana; Lindawati Lindawati (Getsempena Health Science Journal, 2025)
Immunization is a way to actively increase a person’s immunity to an antigen, so that later he or she will not be exposed to a similar antigen (Hardinegoro, 2018). The role of parents in promotive health efforts for those aged 0-11 months is very important, especially in fulfilling the completeness of basic immunization, so that the baby can be free from Diseases that Can Be Prevented by Immunization One of the programs that has been proven effective in reducing morbidity and mortality. The purpose of this study was to determine the Factors Affecting Incomplete Immunization of Infants in Firdaus Village, Si Rampah District. The population of this study were mothers who had babies aged 9-12 months who lived in Firdaus Village, Si Rampah District. This study was descriptive analytical to determine “Factors Affecting Incomplete Immunization of Infants in Firdaus Village, Si Rampah District in 2022”, with a cross-sectional design (cross-sectional), where independent and dependent variables were collected simultaneously. The relationship between mother’s attitude towards Incomplete immunization in infants was obtained in this study. The results of the Chi-Square test (X2) were 9.458 with a CI of 95% and 0.05 where P (0.002) (0.05). 5. The realtionship between family support and Incomplete immunization in infants was obtained in this study. The results of the Chi-Square test (X2) were 5.102 with a CI of 95% and 0.05 where P (0.024) (0.05).